Gelsolin Modulates Platelet Dense Granule Secretion and Hemostasis via the Actin Cytoskeleton - Paul, Manoj; Golla, Kalyan; Kim, Hugh (Thrombosis and Haemostasis, 2022)
Background and Objective The mechanisms underlying platelet granule release are not fully understood. The actin cytoskeleton serves as the platelet's structural framework that is remodeled upon platelet activation. Gelsolin is a calcium-dependent protein that severs and caps existing actin filaments although its role in modulating platelet granule exocytosis is unknown.Methods The hemostatic function of wild-type (WT) and gelsolin null (Gsn−/−) mice was measured ex vivo by rotational thromboelastometry analysis of whole blood. Platelets were purified from WT and Gsn−/− mouse blood and activated with thrombin. Platelet aggregation was assessed by light-transmission aggregometry. Clot retraction was measured to assess outside-in integrin signaling. Adenosine triphosphate (ATP) release and surface P-selectin were measured as markers of dense- and α-granule secretion, respectively.Results The kinetics of agonist-induced aggregation, clot retraction, and ATP release were accelerated in Gsn−/− platelets relative to WT. However, levels of surface P-selectin were diminished in Gsn−/− platelets. ATP release was also accelerated in WT platelets pretreated with the actin-depolymerizing drug cytochalasin D, thus mimicking the kinetics observed in Gsn−/− platelets. Conversely, ATP release kinetics were normalized in Gsn−/− platelets treated with the actin polymerization agonist jasplakinolide. Rab27b and Munc13–4 are vesicle-priming proteins known to promote dense granule secretion. Co-immunoprecipitation indicates that the association between Rab27b and Munc13–4 is enhanced in Gsn−/− platelets.Conclusions Gelsolin regulates the kinetics of hemostasis by modulating the platelet's actin cytoskeleton and the protein machinery of dense granule exocytosis.
Keywords: platelet physiology; secretion; exocytosis; cytoskeleton